The Role of Legal Aid Institutions in Supporting Access to Justice for Underprivileged Communities - Flora, Henny Saida; Hasnia, Hasnia; Lubis, Arief Fahmi; Sarjono, Anastasia; Puwa, Suryani Intan Pratiwi (Civiliza Publishing, 2024)
One of the factors that should be considered in the legal protection of the poor is the equal position of citizens before the law. In a just society, there should be no gap between the people and those who have money and positions that afford them the same status as citizens in accordance with the legal system. It is imperative that legal aid be made available to impoverished individuals and communities in a criminal justice system that has yet to achieve comprehensive integration. The objective of this research is to ascertain the role of consultation and legal aid institutions in providing legal assistance and community empowerment for economically disadvantaged individuals. This research employs an empirical juridical approach to examine the activities of the Consultation and Legal Aid in fulfilling its role. The findings indicate that the Institute for Consultation and Legal Aid is obliged to provide assistance to legal aid providers free of charge. However, information regarding the provision of free or low-cost legal aid has not been widely disseminated, resulting in a significant number of defendants or suspects who are dealing with the law and do not receive assistance from legal aid providers. This lack of access to legal aid services leaves individuals without the means to effectively navigate accusations, suspicions, or charges from the state, thereby exacerbating their vulnerability.